(untitled) (Research, Society and Development, 2021)
Introduction: Aging contributes to a greater susceptibility of the elderly to sexually transmitted infections (STIs), due to organic changes that occur at this stage of life and to the prolongation of sexual life. Objective: In this sense, this research aimed to evaluate the clinical and epidemiological profile of elderly people infected with HIV. Methodology: This is a documentary, retrospective study, which had 107 elderly individuals with HIV infection as subjects. The development site was the State Center for Specialized Care (CEAE), located in the city of Patos de Minas, in Minas Gerais, Brazil. For data collection, medical records were consulted, using a form containing sociodemographic, epidemiological and clinical information. Data were organized in Excel spreadsheets and analyzed using the Statistical Package for Social Science (SPSS – 14.0) software. This research was approved by the Research Ethics Committee of the University Center of Patos de Minas (UNIPAM) under protocol number 3.169.404. Results: Most of the elderly were married, heterosexual, had an occasional sexual partner and did not use condoms; in addition, they had no history of other STIs or injecting drug use. Finally, the most prevalent comorbidities were systemic arterial hypertension, dyslipidemia, diabetes mellitus, thyroid diseases and depression. Conclusion: The profile of elderly people with HIV infection in the interior of Minas Gerais was people with an average age of 64 years, predominantly male, with incomplete elementary education and retired.